Unveiling the active sites of graphene-catalyzed peroxymonosulfate activation - Duan, X.; Sun, Hongqi; Ao, Z.; Zhou, L.; Wang, G.; Wang, S. (Pergamon, 2016)
Graphene-based materials have emerged as novel and green alternatives to metals/oxides for environmental catalysis. This study integrates deliberate material fabrication with density functional theory (DFT) calculations to probe intrinsic active sites, e.g. the defects and oxygen functionalities on graphene for activating O-O bond in peroxymonosulfate (PMS) toward catalytic oxidation. The reaction rate constants of degradation efficiency were discovered to be closely related with the ID/IG values of thermally annealed reduced graphene oxides (rGOs). Three rGOs (rGO-CM, rGO-HH, and rGO-HT) with a similar oxygen level by different reduction methods were utilized to investigate the effect of different oxygen groups. The results indicate that rGO-HT with the highest contents of ketonic group (C=O) presented the best activity. The theoretical calculations were applied to simulate the PMS chemisorption with all the possible active sites on rGO. The DFT results suggest that vacancies and defective edges are more reactive than the graphene basal plane with prolonged O-O bond in PMS molecules, greater adsorption energy, and more electron transfer. Besides, the electron-rich ketonic groups may be the major active species among the oxygen functionalities. The findings will contribute to new insights in reaction mechanism and material design in heterogeneous carbocatalysis.